Desenvolvimento e comparação de ferramentas e pipelines para análises ômicas nos estudos de conservação da diversidade vegetal - Renato Renison Moreira Oliveira (2023)
Plants play a key role in maintaining life on the planet, and in the face of threats, mainly anthropogenic, it is essential to conduct conservation studies to ensure the knowledge, protection, and perpetuation of species. Among the various approaches in these studies, Conservation Genetics and Genomics stand out, the latter being able to provide information that allows a better understanding of adaptive characteristics, genetic variability and adaptive studies under different environmental stresses. Conservation Genomics gained greater relevance with the emergence of sequencing technologies, allowing an exponential growth in the amount of genomes deposited in public databases. Although the costs of sequencing have decreased considerably and the amount of data generated has increased, assembling large genomes of eukaryotes, especially plants, is still a complex and costly activity. Inherent characteristics of plant genomes, such as polyploidy, genome size, and repetitive regions still cause problems in the assembly processes of these genomes. To solve these problems, a great diversity of assembly software has been developed, each one working in a specific way. Besides the development of several software assemblers to overcome these problems in assembling large and complex genomes, other techniques that have been developed and widely used in biodiversity studies are the barcoding and metabarcoding techniques, which together allow the rapid and accurate identification of species present in environmental samples, as well as to perform evolutionary studies. This work identified three needs in the areas of environmental genomics and, through the elaboration of three articles, sought to supply those needs. The first paper introduces SPLACE, a tool that allows for the alignment and concatenation of genes in an automated, fast, and accurate manner, addressing missing data and generating a supermatrix that can be used for the inference of phylogenomic trees. The second paper presents PIMBA, a pipeline to conduct metabarcoding analyses quickly and comprehensively, allowing users to choose different analysis approaches and their various parameters, and also facilitating the use of one's own reference databases, in addition to the existing traditional databases and GenBank. Lastly, a manuscript was produced aiming to fill a gap in the literature by fairly comparing the various genome assemblers available for several plant species and gathering information about the complete nuclear genomes of plants that have already been analyzed. These three published works assisted in various important studies planning strategies for the conservation of plant diversity and can also be applied to other groups of organisms.